Psychological and pedagogical support of educators-to-be in speech development of young children - Kondratets, Inna; Naumenko, Maryna (Educological discourse, 2022)
The article defines the essence of the concept of "psychological-pedagogical support" as a complex system of activities for the organization of optimal conditions and partner support on the part of teachers, realizing opportunities for self-discovery, revealing the creative potential, abilities, inclinations, interests and motives, forming a sense of self-worth and striving for self-realization through the active application of scientific achievements for each student of higher educational institution. The main emphases of scientists regarding interaction with young children in the field of speech development, which should be taken into account by practitioners, are analyzed: the existence of two parallel spheres of speech communication: communication with adults and communication with children; the effect of imitating the speech of an adult; considering speech as an accompanying activity without which no other child's activity can take place fully. Numerous approaches that ensure the effectiveness of psychological and pedagogical support of educators-to-be in planning and organizing forms of interaction with young children are highlighted: reflexive, axiological, competence-based. The algorithm for psychological and pedagogical support of educators-to-be is outlined: determination of the level of ideas and awareness of the psychological characteristics of young children; awareness of the patterns of speech development of young children; understanding the differential selection of effective forms of interaction with children, giving preference to modern methods and techniques; modeling of forms of partnership interaction with parents of pupils; case testing of various forms of interaction during practical training in early childhood groups; presentation of positive experience in various educational circles. The peculiarities of modern forms of interaction with children are analyzed, attention on indirect and direct forms of interaction on the development of speech is focused.